65.5k views
0 votes
What is the result of subtracting the second equation from the first? \begin{aligned} x-3y &= 6 \\\\ -8x-y &= 6 \end{aligned} x−3y −8x−y ​ =6 =6 ​

2 Answers

3 votes

Answer:

nani

Explanation:

User Twopheek
by
5.4k points
6 votes

Answer:

Therefore the required result is 9x-2y =0.

Explanation:

Given equation are

x-3y =6.....(1)

-8x-y=6 .....(2)

Subtracting equation (2) from (1)

x - 3y = 6

-8x - y= 6

+ + - [ The sign of equation (2) will be change in case of

_________ subtraction and in case of plus the signs remains same ]

(x+8x)-3y+y=6-6 [ adding the like terms]

⇒9x-2y =0

Therefore the required result is 9x-2y =0.

User Peterson
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.